2010
DOI: 10.1002/pi.2963
|View full text |Cite
|
Sign up to set email alerts
|

Chemically bonded iron carbonyl for magnetic composites based on phthalonitrile polymers

Abstract: Dicarboxylic acid-containing 1,3-benzoxazine was synthesized and chemically bonded on iron carbonyl particles using a post-coating method. Novel organic-inorganic hybrid magnetic composites were prepared via the interfacial reaction between magnetic phthalonitrile prepolymers and the benzoxazine functional coatings that chemically modified the iron carbonyl particles. The results showed that, compared with pure iron carbonyl particles, the modified particles could cure the phthalonitrile prepolymers efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…The FTIR data revealed that the characteristic absorption peak of the nitrile band at 2231 cm −1 gradually decreased, which are attributed to an increase of curing temperature and time. It was consistent with a typical feature of polymerization of phthalonitrile polymers [30]. In addition, a weak peak assigned to the triazine absorption at 1520 cm −1 showed a small increase in intensity as the curing temperature and time increased.…”
Section: Thermal Properties Of 3-apn Polymerssupporting
confidence: 72%
“…The FTIR data revealed that the characteristic absorption peak of the nitrile band at 2231 cm −1 gradually decreased, which are attributed to an increase of curing temperature and time. It was consistent with a typical feature of polymerization of phthalonitrile polymers [30]. In addition, a weak peak assigned to the triazine absorption at 1520 cm −1 showed a small increase in intensity as the curing temperature and time increased.…”
Section: Thermal Properties Of 3-apn Polymerssupporting
confidence: 72%
“…The easy processability of the phthalonitrile monomers into void-free thermosets with a number of exceptional properties, such as a high glass transition temperature, outstanding thermal and thermo-oxidative stabilities, excellent mechanical properties, good moisture, and fire resistant performance [3][4][5], allowed these types of resins to be used as an advanced composites matrices, adhesives, carbon precursors, and microelectronic packing materials [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This high performance resin has been widely used in different applications such as in composites [10], as a carbon precursor [11], and in microelectronic packaging [12].…”
Section: Introductionmentioning
confidence: 99%